eSocial deployment in thehuman resources sector: a case study (Research, Society and Development, 2020)
eSocial is designed to ensure that company employee information is passed on the government to control the movements of an organization. The objective of this paper is to identify the main difficulties encountered during the eSocial deployment process and the advantages and disadvantages of using the system. For this, a case study was conducted through an interview with the professional responsible for Human Resources in a company that operates in the industrial sector in the region of Campinas/SP. There were no problems during the system deployment process. Among the advantages is the fact that the company sends information in real time, which means that tasks do not accumulate over time. The main disadvantage mentioned by the company was related to sending information to eSocial and other government-required systems such as Sefip and Caged.